A Longitudinal Examination of Decisions to Ride and Decline Rides with Drinking Drivers. (13th July 2018) - Hultgren, Brittney A.; Turrisi, Rob; Mallett, Kimberly A.; Ackerman, Sarah; Larimer, Mary E.; McCarthy, Denis; Romano, Eduardo
Abstract : Background: Riding with a drinking driver (RWDD) is a serious concern that leads to numerous preventable deaths every year. There is a significant gap in research on empirically tested predictors of RWDD that could be implemented in prevention efforts. College students are in need of such prevention efforts, as they have some of the highest rates of alcohol‐related crash fatalities and may engage in RWDD more than their noncollege peers. This study utilized behavioral decision‐making approach to examine predictors of RWDD and declining a ride from a drinking driver (Decline) in older college students. Methods: Students ( n  = 791) in their third year of college were enrolled from 3 large and diverse universities. Psychosocial (e.g., expectancies, norms) and decision‐making variables (willingness to RWDD and intentions to use alternatives) were assessed in the fall of their third year. One year later, RWDD and Decline behaviors were assessed. Zero‐inflated Poisson analyses were used to assess how decision‐making variables predicted RWDD and Decline behavior. Associations between psychosocial and decision‐making variables were also assessed. Results: Thirteen percent of students reported RWDD and ~28% reported Decline behavior. Willingness to RWDD and typical weekly drinking were both associated with increases in RWDD (odds ratio [OR] = 1.58 and 1.40, respectively), whereas intentions to use alternatives, sex, and ethnicity were not associated with RWDD. Only weekly drinking was associated with Decline, with an increase in drinking associated with increased Decline (OR = 1.48). All psychosocial variables were significantly associated with the decision‐making variables except positive expectancies. Conclusions: Results provide evidence that willingness to RWDD is a predictor of future RWDD, even if students intend to use safe alternatives. Future research is needed to better understand decision‐making factors that influence Decline. Results also suggest prevention and interventions efforts, such as brief motivational intervention, Parent‐Based Interventions, and normative feedback interventions could be adapted to reduce RWDD. Abstract : Decision‐making variables were assessed as predictors of riding with a drinking driver (RWDD) and declining a ride from a drinking driver (Declining). Solid lines indicate hypothesized positive association and dotted lines indicate hypothesized negative associations. Only willingness to RWDD was associated with RWDD and neither construct was associated with Declining. Results suggest even if students intend to use safe alternatives they may still be at risk of RWDD if they are willing to RWDD. Prevention implications are discussed.